Implikasi Pengaturan Baru Tindak Pidana Perzinahan terhadap Perlindungan Hak Asasi Manusia di Indonesia: Penelitian - Rian Prayudi Saputra (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
The changes to the criminal provisions for adultery in the New Criminal Code (Law No. 1 of 2023) have sparked debate regarding the relationship between public morality and human rights protection. This reformulation represents a significant shift from the Old Criminal Code, particularly in expanding the scope of the offense, reporting subjects, and strengthening norms of order and morality. This study aims to analyze the implications of the new provisions for adultery on human rights principles, particularly the rights to privacy, non-discrimination, individual autonomy, and family protection, and to assess their compliance with the principles of the rule of law, the balance between public morality and individual freedom, and the limits of legitimate human rights restrictions. The method used is normative legal research with a legislative, conceptual, and analytical approach, using sources from regulations, criminal law literature, human rights instruments, court decisions, and analysis of official institutions. The results of the study indicate fundamental differences between the Old and New Criminal Codes, particularly in the expansion of the criminalization of extramarital sexual relations and the increase in the number of complainants. This expansion creates the potential for family conflict, misuse of complaints, and the criminalization of the private sphere. From a human rights perspective, this could violate the right to privacy, personal liberty, and the principle of non-discrimination, particularly for couples without registered marriages. However, the offense of complaint remains a relative barrier to prevent repressive use of criminal law. Challenges also arise in terms of evidentiary aspects, the capacity of authorities, and the diversity of societal values. The study concluded that although the new regulation is intended to strengthen morality and family order, it has the potential to conflict with human rights principles if not implemented carefully. Therefore, harmonization of morality, legal certainty, and respect for human rights is necessary to ensure that the implementation of the New Criminal Code does not violate citizens' fundamental freedoms.